The Role of Apelin–APJ System in Diabetes and Obesity - Li, Cheng; Cheng, Hongna; Adhikari, Binay Kumar; Wang, Shudong; Yang, Na; Liu, Wenyun; Sun, Jian; Wang, Yonggang (Frontiers in Endocrinology, 2022)
Nowadays, diabetes and obesity are two main health threatening metabolic disorders in the world, which increase the risk for many chronic diseases. Apelin, a peptide hormone, exerts its effect by binding with angiotensin II protein J receptor (APJ), and is considered to be linked with diabetes and obesity. Apelin and its receptor are widely present in the body, and are involved in many physiological processes, such as glucose, and lipid metabolism, homeostasis, endocrine response to stress and angiogenesis. In this review, we summarize the literatures on the role of Apelin-APJ system in diabetes and obesity, for better understanding of the mechanism and function of apelin and its receptor in pathophysiology of diseases that may contribute to the development of new therapies.